Mine haul road design and management best practices for safe and cost-efficient truck haulage - Thompson, Roger (Society for Mining, Metallurgy and Exploration, 2010)
Well designed and maintained haul roads are the key to minimizing truck haulage on-road hazards and costs, as well as increasing productivity. However, practically designing and managing a haul road for optimal performance is often difficult to achieve. Poorly designed and built roads exhibit high rolling resistance - a 1% increase in road rolling resistance can typically reduce speed on ramp by as much as 10% - and on the flat by up to 26%. In the current economic climate, investment and operating decisions come under scrutiny. In the long run, this scrutiny returns improved efficiencies and leaner, healthier operations. The focus of this evolving evaluation process should and will certainly fall on haulage operations - simply by virtue of their contribution to overall cost of operations - often in excess of 50% of total costs for deep open-pit mines.Whilst the end result - improved efficiency and reduced cost per ton hauled - is not in itself problematic, it is the route, or process followed to achieve these savings that needs to be carefully managed. We can be guided on this journey by our understanding of how a road design is developed, and, critically, the interplay between a good design and safe, cost efficient haulage.This paper briefly summarizes the evolution of mine haul road design, from the seminal USBM work of Kaufman and Ault in 1977, through to current geometric, structural, functional and maintenance management design components. These augmented design and management guidelines have been developed over the past decade, both in response to the requirements of mine operators for more safe and efficient haulage systems, and the truck manufacturers - requirements for a more predictable and controlled operating environment.These developments have been paralleled by the need to minimize haulage hazards, both from a health and safety perspective. Whilst improved mine haul road design does indeed reduce haulage accidents, recognition also needs to be given to human factors which are a significant contributor to haulage accidents. The human factor is the most problematic to address in a road design. It is often easier break the link between the interactive effects which may lead to accidents than trying to predict and reduce human error. These human factor interactive effects include the geometric, structural and functional design components and to prevent an accident or reduce the severity of its consequences, a road should be more accommodating to human error. The more that is known about human error, the better a road can be designed to accommodate those actions or non-standard practices that would, on a poorly designed road, invariably escalate an error into an accident.